PEMBELAJARAN DI SEKOLAH DASAR DARI PRESPEKTIF MULTILITERASI DAN KETERAMPILAN BERPIKIR TINGKAT TINGGI (KBTT) - Tatat Hartati (Jurnal Inovasi Sekolah Dasar, 2020)
The 21st century needs quality human resources to respond to the changes in the industrial revolution era 4.0. These all-new demands require breakthroughs in terms of thinking and action if you want quality output that can compete with global and open-ended global work. However, the facts show that Indonesia's latest literacy ranking is in the second position from the bottom of the 61 countries studied. Indonesia is only better off Bostwana, a country in the South African region. In terms of reading skills, the INAP concludes, among others: students are not accustomed to answering questions that require high level interpretation and special terms (non common sense), texts that require the ability to imagine, explain, and have opinions. Thus, multiliteracy education and higher order thinking skills (KBTT) need to be intensified.Key words: multiliteration, higher order thinking